HIV-1 Nef interferes with T-lymphocyte circulation through confined environments in vivo - Stolp-Rastätter, Bettina; Imle, Andrea; Fackler, Oliver Till (Proceedings of the National Academy of Sciences of the United States of America, 2012)
HIV-1 negative factor (Nef) elevates virus replication and contributes to immune evasion in vivo. As one of its established in vitro activities, Nef interferes with T-lymphocyte chemotaxis by reducing host cell actin dynamics. To explore Nef’s influence on in vivo recirculation of T lymphocytes, we assessed lymph-node homing of Nef-expressing primary murine lymphocytes and found a drastic impairment in homing to peripheral lymph nodes. Intravital imaging and 3D immunofluorescence reconstruction of lymph nodes revealed that Nef potently impaired T-lymphocyte extravasation through high endothelial venules and reduced subsequent parenchymal motility. Ex vivo analyses of transendothelial migration revealed that Nef disrupted T-lymphocyte polarization and interfered with diapedesis and migration in the narrow subendothelial space. Consistently, Nef specifically affected T-lymphocyte motility modes used in dense environments that pose high physical barriers to migration. Mechanistically, inhibition of lymph node homing, subendothelial migration and cell polarization, but not diapedesis, depended on Nef’s ability to inhibit host cell actin remodeling. Nef-mediated interference with in vivo recirculation of T lymphocytes may compromise T-cell help and thus represents an important mechanism for its function as a HIV pathogenicity factor.